Adriamycin-Induced Nephropathy is Robust in N and Modest in J Substrain of C57BL/6 - Bryant, Claire; Cianciolo, Rachel; Govindarajan, Rajgopal; Agrawal, Shipra (Frontiers in Cell and Developmental Biology, 2022)
Adriamycin (ADR)-induced nephropathy remains the leading model to study human primary focal segmental glomerulosclerosis (FSGS), a common pathway for podocyte damage and glomerular loss of function that leads to chronic kidney disease. However, the use of this model for reverse genetics is limited by historical categorization of C57BL/6 mice as an ADR-resistant strain, which is also the most common genetically modified strain. Additionally, conflicting reports exist utilizing C57BL/6 for ADR-nephrosis due to lack of understanding of substrain differences (J/N) and variability in ADR dosage, timing, and frequency to induce damage. We have undertaken a systematic approach to elucidate the specifics of ADR-nephrosis in C57BL/6 N and J substrains. We induced nephropathy with 2 doses of ADR, and measured albuminuria for 6 weeks and performed histological evaluations. Our findings revealed induction of robust and modest proteinuria in N and J substrains, respectively. The serum creatinine levels were elevated in N, but not J substrain. Both the substrains showed reduction in body weight with N greater than J, although mortality remained at 0% in both substrains. Histological analysis showed worse renal lesions in the N than the J substrain. Podocyte markers synaptopodin, nephrin, podocin, and WT1 were reduced to a greater extent in the N than the J substrain. In summary, we provide the nephrology community with a reproducible mouse model for FSGS, in a strain otherwise assumed to be ADR-resistant and highlight the differences between J and N substrains. This enables future studies, especially concerning genetically manipulated animal models in C57BL/6.